2021
DOI: 10.1097/tp.0000000000003328
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Intestinal Transplantation Compared to Parenteral Nutrition in Adults

Abstract: Background: Intestinal Transplantation (ITx) is the most expensive abdominal organ transplant. Detailed studies about exact costs and cost-effectiveness compared to home parenteral nutrition (HPN) therapy in chronic intestinal failure (CIF) are lacking. The aim is to provide an in-depth analysis of ITx costs and evaluate cost-effectiveness compared to HPN. Methods: To calculate costs before and after ITx, costs were analyzed in 12 adult patients. To calculate costs of patients with uncomplicated CIF, 28 adult,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…After transplant, hospitalization costs decreased each year during the first 3 years. These results mirror what has been reported in a Belgian adult cohort 14 . Although median hospitalization costs up to 3 years after transplant seemed to be higher than pretransplant costs, this only represents a portion of the total healthcare for expenditure for these children.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…After transplant, hospitalization costs decreased each year during the first 3 years. These results mirror what has been reported in a Belgian adult cohort 14 . Although median hospitalization costs up to 3 years after transplant seemed to be higher than pretransplant costs, this only represents a portion of the total healthcare for expenditure for these children.…”
Section: Discussionsupporting
confidence: 87%
“…These results mirror what has been reported in a Belgian adult cohort. 14 Although median hospitalization costs up to 3 years after transplant seemed to be higher than pretransplant costs, this only represents a portion of the total healthcare for expenditure for these children. Home parenteral nutrition alone has yearly costs estimated to exceed $150,000, 15 and yearly maintenance immunosuppression costs after transplant have been estimated as $12,000 for renal transplant.…”
Section: Alternatively T-cell-depleting Antibody Use Could Intrinsica...mentioning
confidence: 97%
“…Median weight was 50 kg . BMI was 19.6 kg/m 2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). BMI was higher than the predefined maximum of 25 kg/ m 2 in one donor.…”
Section: Intestinal Donor Criteria Used In Our Itx Cohort Are Less St...mentioning
confidence: 91%
“…In three donors, CPR had been performed for 20 min (10-30) and cardiac arrest time in these donors was 25 min (5-45). Hypotensive episodes of 10 min were noted in two donors (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Norepinephrine was used at a dosage of 0.1 μg/kg/min (γ) (0.0155-0.68) as single inotropic in 13 donors and in combination in 2 others.…”
Section: Intestinal Donor Criteria Used In Our Itx Cohort Are Less St...mentioning
confidence: 99%
“…However, most patients are weaned off parenteral nutrition before discharge. It has been shown that ITx is cost-saving compared to PN in the medium to long term (5 years) [37 ▪ ].…”
Section: Cost Effectiveness Outcomes and Quality Of Life Considerationsmentioning
confidence: 99%